Association of RANTES gene polymorphisms with susceptibility to childhood asthma: A meta-analysis. Issue 29 (17th July 2020) - Zhang, Yan-Qin; Gao, Xiu-Xiang
Abstract: Background: Previous investigations have illustrated that regulated upon activation, normal T-cell expressed and secreted (RANTES) polymorphisms are linked to susceptibility to childhood asthma; nevertheless, the findings continue to be controversial. Accordingly, we conducted the present meta-analysis to clarify the impact of RANTES genetic polymorphisms (-403G/A and -28C/G) on childhood asthma vulnerability. Methods: A search for published literature was performed using the PubMed, EMBASE, Chinese National Infrastructure, Cochrane Library, Scopus, Web of Science, and WanFang databases and selected in the form of PICOS (participants, interventions, comparisons, outcomes, and study design) to identify all eligible research works. The link between RANTES genetic polymorphisms and childhood asthma susceptibility was evaluated by a pooled odds ratio with a 95% confidence interval. Results: In total, 14 case–control studies were included in the analysis. No significant association existed between risk of childhood asthma and the -403G/A polymorphism subjected to any genetic framework in the overall population. In the stratified analysis, according to ethnicity, the -403G/A polymorphism was linked to augmented vulnerability to childhood asthma in Caucasians (allelic model: odds ratio [OR] = 1.63, 95% confidence interval [CI] = 1.04–2.57, P  = .034; codominant model: OR = 2.20, 95% CI = 1.28–3.78, P  = .004; dominant model: OR = 1.78, 95% CI = 1.01–3.13, P  = .047; and recessive model: OR = 1.92, 95% CI = 1.11–3.30, P  = .019). For the stratified analysis by atopic status, the -403G/A polymorphism was linked to augmented childhood asthma in the codominant (OR = 1.39, 95% CI = 1.02–1.91, P  = .037) and dominant models (OR = 1.43, 95% CI = 1.02–2.01, P  = .037) in atopic asthma. For the -28C/G polymorphism, there was a significant association between childhood asthma and the -28C/G variant (allelic model: OR = 1.33, 95% CI = 1.08–1.65, P  = .009; codominant framework: OR = 2.14, 95% CI = 1.47–3.10, P  < .001; dominant model: OR = 1.44, 95% CI = 1.07–1.93, P  = .017; and recessive model: OR = 2.08, 95% CI = 1.44–3.02, P  < .001). Stratified analysis based on ethnicity and the -28C/G polymorphism was linked to augmented vulnerability to childhood asthma in Asian and Caucasian populations. For the subgroup analysis by atopic status, no association was found in atopic and non-atopic asthma. Conclusion: The present meta-analysis indicated that the RANTES -403G/A and -28C/G polymorphisms contributed to the development of childhood asthma.